Effect of Peri-Ovulatory Endocrine Milieu in the Oviductal Physiology of Beef Cows: Regulation of the Transcriptome, Tissue Morphology, Cell Proliferation, Extracellular Matrix Remodeling, microRNAs Abundance Profile, and Oviductal Fluid Composition - Diaza, Angela Maria Gonella (2017)
In cattle, the oviduct plays an important role in the reproductive process. Oviductal secretions characterize the environment where storage and sperm capacitation, fertilization, and early embryo development take place. Because molecular control of bovine oviduct receptivity is poorly understood, this Thesis proposed a model of receptivity based on the manipulation of pre-ovulatory follicle growth (POF) used to study the effects of periovulatory endocrine profile on oviductal physiology. Growth of POF in Nelore cows (Bos indicus) was manipulated to produce two groups: cows with large POF and large corpus luteum (LF-LCL; higher fertility) and cows with small POF and small CL (SF-SCL; Lower fertility). Ampulla and isthmus samples were collected on day 4 after induction of ovulation with GnRH. In the first study, the transcriptome of the ipsilateral to CL ampulla and isthmus was determined by RNAseq, the regional expression of genes was studied by qPCR, and the distribution of the PGR and ER proteins was assessed by immunohistochemistry. Greater abundance of PGR and ER was found in the oviduct of the LF-LCL animals indicating that there is a greater availability of receptors and, possibly, of signaling-mechanisms stimulated by steroids in both oviductal regions. The transcripts profile showed enriched oviductal functional characteristics that could affect its embryo receptivity. These characteristics include changes in morphology i.e. branching morphogenesis, and changes in cell functioning i.e. cell secretion, that were enriched in the LF-LCL group. In the second study, after morphological analyses, it was concluded that the ampulla of the LF-LCL animals presented more primary folds, a larger perimeter of the luminal epithelium, and a higher proportion of secretory and proliferating cells, when compared to SF-SCL group. There was no difference in isthmus morphology between groups. In the third study, the extracellular matrix remodeling was reserched. It was concluded that in the isthmus region of the LF-LCL animals, there is less type 1 collagen fibers and greater abundance of proteins involved in extracellular matrix remodeling. In the fourth study, it was determined that the periovulatory endocrine milieu affects the expression of components of the microRNAs biosynthesis pathway and the microRNAs profile, both different between groups. Finally, in the fifth study, 205 metabolites were quantified in the oviductal fluid and 37 were found to be in different concentrations when both groups were compared. It was concluded that oviduct of cows of higher fertility presents a profile of transcripts, proteins, and metabolites that is associated with morphological and functional characteristics favorable to the survival and development of the embryo.